Use of transcriptomics and genomics to assess the effect of disinfectant exposure on the survival and resistance of Escherichia coli O157:H7, a human pathogen - Kirchner, Miranda; Nunez-Garcia, Javier; Duggett, Nicholas; Gosling, Rebecca J.; Anjum, Muna F. (Frontiers in Microbiology, 2024)
Disinfectants are essential for biosecurity, preventing persistence and spread of zoonotic pathogens on farm, and subsequent human infections. In this study, transcriptomics and genomics were utilised to assess the effect of disinfectant exposure on pathogenic Escherichia coli. Exposure of E. coli O157:H7 to sub-optimal concentrations of commonly used farm disinfectants elicited changes in the transcriptome and genome. Transcriptomics identified upregulation of >300 and downregulation of >100 genes with functions which included stress response, metabolism, transcription, transportation, membrane-associated and virulence genes. The phage shock operon (psp) was highly upregulated in response to quaternary ammonium compound containing disinfectant, which has not previously been associated with response to chemical stress. Disinfectant adapted isolates generated by exposure to sub-lethal disinfectants levels, demonstrated resistance to several common antibiotics, as well as decreased sensitivity to biocides. Whole genome sequencing of mutant strains indicated that they had acquired mutations in genes associated with upregulation of the MAR efflux system (lon protease and marR) and topoisomerase genes (gyrA and gyrB).Disinfectant adapted isolates also had increased expression of transcription, respiration, and several pH stress response genes localised in the "acid fitnessisland". This study demonstrated that sub-optimal disinfectant concentrations allow E. coli O157:H7 to adapt and survive disinfection and develop antibiotic resistance. These changes could have implication for treatment of disease and elimination on farm. Although E. coli O157:H7 and farm disinfectants were used in this study we believe these findings are also applicable to other settings including hospitals.